Investigating the Relationship Among Coronavirus Anxiety, Smartphone Addiction, and Sleep Quality During Covid-19 Pandemic - Öztürk, Zeynep; Aksoy, Meyreme; Turan, Gülcan Bahçecioğlu (My University, 2023)
Objective: This research aimed to examine the correlations between coronavirus anxiety, smartphone addiction, and sleep quality during the COVID-19 pandemic. Material and Methods: This study had a cross-sectional and correlational design. Snowball sampling was used. Data collection was done online with individuals from different cities around Türkiye between May – June 2021. The study was completed with 684 participants in total. For data collection, a personal information form, the Coronavirus Anxiety Scale, the Smartphone Addiction Scale, and the Richards-Campbell Sleep Questionnaire were used. In the evaluation of the data, number, mean, percentile distributions, standard deviation, Pearson Correlation analysis and Linear Regression analysis were used. Results: The participants had mean scores of 2.33±3.34 for the Coronavirus Anxiety Scale, 33.33±11.69 for the Smartphone Addiction Scale, and 61.29±22.75 for the Richards-Campbell Sleep Questionnaire. We found a negative correlation between mean sleep quality scores and mean coronavirus anxiety and smartphone addiction levels and a statistically significant positive correlation between mean coronavirus anxiety and smartphone addiction scores. Conclusion: This study revealed some correlations between coronavirus anxiety, smartphone addiction, and sleep quality in the general population during the COVID-19 pandemic. As coronavirus anxiety increased, sleep quality was found to decrease and smartphone addiction to increased. Besides, sleep quality was reduced as smartphone addiction increased
Keywords: COVID-19; Anxiety; smartphone; sleep